Effectiveness of Oral Magnesium in improving in-Hospital Outcome in patients presenting with Acute Exacerbation of Chronic Obstructive Pulmonary Disease - Sohail Bashir Sulehria, Hafiza Farah Masood, Muhammad Kamran Yousaf, Nasir Hussain, Masooma Batool, Ch Adnan Ahmed Athar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To study effectiveness of oral magnesium in improving in-hospital outcome in patients presenting with COPD exacerbation. Study Setting: It was conducted at Department of Medicine, Mayo Hospital, Lahore. Duration of study: Six month following approval of synopsis Study design: Comparative Cross-Sectional Methods: Total 160 patients who fulfilled the inclusion criteria were selected . All patients regardless of the group were given conventional management in the form of oxygen inhalation, anti-cholinergic and beta-2 agonist nebulization, intravenous steroids as well as steroid nebulization and intravenous antibiotics. In addition, Group-A was given magnesium in the form of 400 mg of magnesium oxide twice daily. Both groups were followed over their time of stay in the hospital to assess effect of oral magnesium. Data were entered and analyzed by SPSS v26.0. Means were compared by applying students t-test. Two groups were compared using Chi-square test. A p-value ≤0.05 was taken as statistically significant. Results: According to outcome distribution between groups, in group-A, 44(55%) patients were discharged, while 24(30%) needed assisted ventilation and 12(15%) expired. In group-B, 58(72.5%) patients were discharged, while 6(7.5%) needed assisted ventilation and 16(20%) expired with a p-value 0.178 ( for discharge), which is not statistically significant Conclusion: Oral magnesium does not effectively improve in-hospital outcome in those who presented with COPD exacerbation in comparison to those not receiving oral magnesium. Keywords: Chronic Obstructive Pulmonary Disease, Acute Exacerbation, Magnesium Sulphate.